Removal of Chlorpyrifos Insecticide by Mix culture Thiobacillus sp. and Clostridium sp.: Implementation Recommendation on Pilot Scale - Astri Rinanti, Rositayanti Hadisoebroto (International Journal of Advanced Science and Technology, 2020)
This research was conducted to degrade soil-polluting chlorpyrifos insecticide by Thiobacillus sp. and Clostridium sp. The aim was to degrade 100 pm of chlorpyrifos during contact with bacteria in a soil during 48, 96, 144, 192, and 240 hours of contact time. Chlorpyrifos removal was analyzed with Gas Chromatography - Mass Spectrophotometry (Agilent DB 35 MS). The research gradually provides information that the mix culture bacteria were able to degrade 100 - 500 ppm of chlorpyrifos with a range of removal efficiency from 17.60% to 98.28%. Initial concentration of chlorpyrifos as much as 59.74 ppm was degraded between 65.18% and 78.50% on 192 hours contact time, field temperature of 27oC to 30oC, pH level of 7.6 and humidity of 27%. Contact time of over 192 hours did not produce degradation result higher than 78.50%. Physical factor such as evaporation play a weak role in chlorpyrifos degradation process. The results of this study have the potential to be applied as a land treatment bioremediation preparation for treating chlorpyrifos-contaminated soil.Keywords: bioremediation, insecticide, Chlorpyrifos, removal of Chlorpyrifos, Thiobacillus sp., Clostridium sp, land treatment.